Development of an agility test for badminton players and assessment of its validity and test-retest reliability - de Franca Bahia Loureiro Jr, L.; Barbosa de Freitas, P. (International Journal of Sports Physiology and Performance, 2016)
Context: Badminton requires open and fast actions toward the shuttlecock, but there is no specific agility test for badminton players with specific movements.